User-Centric Development of Good Delivery Applications Using Design Thinking and Business Model Canvas - Andry, Johanes Fernandes; Lee, Francka Sakti; Christianto, Kevin; Purnomo, Yunianto; Chakir, Aziza; Liliana, Lydia (EAI Endorsed Transactions on Scalable Information Systems, 2025)
INTRODUCTION: The development of internet technology drives companies to innovate and integrate technology into business processes. This study focuses on designing a goods delivery management application using a combination of Design Thinking and the Business Model Canvas (BMC). Design Thinking emphasizes user needs, while BMC ensures business sustainability. Through stages of empathizing, defining, ideating, and prototyping, this research maps user needs, business requirements, and application frameworks to address inefficiencies and modernize goods delivery processes, improving accuracy and operational effectiveness. OBJECTIVES: This research is to design a goods delivery management application by combining Design Thinking and the BMC to align user needs with business goals, addressing inefficiencies, and improving operational processes and data accuracy. METHODS: The research method includes five stages: literature study, data collection (empathize), problem analysis (define), ideation (solution sketch, wireframe, user flow), and prototyping. This approach combines Design Thinking and BMC to address user and business needs. RESULTS: Defining business process inefficiencies, creating user personas and empathy maps, developing user journey maps and information architecture, designing wireframes and user flows, and proposing a Business Model Canvas (To Be). CONCLUSION: The study highlights inefficiencies in goods delivery processes and proposes a new BMC strategy, emphasizing user-centric application development, real-time updates, resource allocation, and modular features, with future recommendations focusing on user experience enhancement and application evaluation.